2022
DOI: 10.3390/su142316119
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Co-Creation of Small and Medium Enterprises, and Service Providers Enabled by Digital Interactive Platforms for Internationalization: A Case Study in Malaysia

Abstract: Small and medium-sized enterprises (SMEs) make an important contribution to their country’s economy, job creation and balance of trade. The government has supported their development through service providers and has encouraged them to participate in the international market. Despite its importance and the encouragement from the government, participation in the international market is low and studies have shown that SMEs struggle to overcome barriers to internationalization. Digital technologies are tools to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 108 publications
1
2
0
Order By: Relevance
“…This can lead to problems with the implementation of new technologies. The study's findings are consistent with Mohamad et al (2022), who found that recruiting skilled workers was a significant barrier to technology innovation among nascent entrepreneurs in Malaysia. The study also found that workforce resistance was a major problem.…”
Section: Resultssupporting
confidence: 89%
“…This can lead to problems with the implementation of new technologies. The study's findings are consistent with Mohamad et al (2022), who found that recruiting skilled workers was a significant barrier to technology innovation among nascent entrepreneurs in Malaysia. The study also found that workforce resistance was a major problem.…”
Section: Resultssupporting
confidence: 89%
“…While they may be more conservative than other funding sources, they are still an option for startups with a solid business plan and a track record of profitability (Gano-an & Chea, 2021). Malaysian banks such as SME Bank, Bank Rakyat and Agro Bank often offer various loan products tailored to the needs of SMEs and startups, making it possible to secure financing for working capital, equipment purchases, or expansion (Mohamad et al, 2022).…”
Section: Sources Of Entrepreneurship Fundingmentioning
confidence: 99%
“…In recent years, new digital technologies such as the internet, websites, mobile applications, and social media have changed the way people interact with each other, especially when it comes to uncertain situations such as the COVID-19 pandemic (Mohamad et al, 2022). Social media functions not just for communication tools but also for businesses.…”
Section: Literature Reviewmentioning
confidence: 99%